Some Manpower Planning Models Based on Levels of Educational Attainment - Balinsky, Warren; Reisman, Arnold (Management Science, 1972)
A number of manpower planning models are developed and optimized. The models are dynamic feed forward models and treat people as the only flow variable. The flow originates by considering a particular population of eligible persons and then traces them through the educational and economic sectors of the model. The flow is driven by selecting the optimal number of entrants into the educational (training) program each period. The objective function is composed of educational and manpower “inventory” costs. The manpower costs are for having an undersupply or oversupply of trained manpower and can be related to unemployment, educational or other societal costs.